Protein dynamical transition in terahertz dielectric response - Markelz, Andrea G.; Knab, Joseph R.; Chen, Jing Yin; He, Yunfen (Chemical Physics Letters, 2007)
The 200K protein dynamical transition is observed for the first time in the terahertz dielectric response. The complex dielectric permittivity ε=ε′+iε″ is determined in the 0.2–2.0THz and 80–294K ranges. ε″ has a linear temperature dependence up to 200K then sharply increases. The low temperature linear dependence in ε″ suggests anharmonicity for temperatures 80K<t<180k, challenging="" the="" assumed="" harmonicity="" below="" 200k.="" temperature="" dependence="" is="" consistent="" with="" thermally="" activated="" sidechain="" motions="" and="" shows="" involved="" in="" dynamical="" transition="" extend="" to="" subpicosecond="" time="" scales.<="" div="">